Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1177/02783649922066402
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Kinematic Solutions for a Fully Parallel Robot with Singularity Robustness

Abstract: In this paper, two inverse-kinematic solutions with singularity robustness for a fully parallel robot manipulator are proposed. First, two inverse-kinematic solutions are presented based on the damped leastsquares method, where the first solution (OSVC) is derived using a velocity constraint, and the other (OSFC) uses a force constraint. It can be shown that both solutions are special cases of a general damped least-squares method (GIKS). Next, under the assumption that direct position measurement is available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is assumed that the platform is tangent to the wave surface. The formulation of inverse kinematic of the Stewart platform can be found in some research by (Merlet 2004), (Liu, Fitzgerald et al 1993), (Perng and Hsiao 1999) and (Salcudean, Drexel et al 1994). To find the inverse kinematics of the mobile plate based on the geometry platform in Figure 5, the coordinates XYZ of points A 1 , A 2 , A 3 , A 4 , A 5 , A 6 must be known, as shown in Figure 5.…”
Section: Inverse Kinematics Of the Stewart Platformmentioning
confidence: 99%
“…It is assumed that the platform is tangent to the wave surface. The formulation of inverse kinematic of the Stewart platform can be found in some research by (Merlet 2004), (Liu, Fitzgerald et al 1993), (Perng and Hsiao 1999) and (Salcudean, Drexel et al 1994). To find the inverse kinematics of the mobile plate based on the geometry platform in Figure 5, the coordinates XYZ of points A 1 , A 2 , A 3 , A 4 , A 5 , A 6 must be known, as shown in Figure 5.…”
Section: Inverse Kinematics Of the Stewart Platformmentioning
confidence: 99%
“…Although the second approach may lead to leg forces that are larger than pre-set limits, it is significantly faster than the first approach. A similar optimization procedure was also proposed by Perng (472), with another penalty constraint, to avoid the singularity. Jui (295) and Ider (261) have shown that if at a singularity the drop of rank of the inverse kinematic jacobian is only one, then it may be possible to control the acceleration so that the forces in the legs remain bounded.…”
Section: Singularity-free Path-planning and Workpace Enlargementmentioning
confidence: 99%
“…However, it is an expensive solution to the problem because of the additional actuators and the complicated control of the manipulator caused by actuation redundancy. Another approach concerns with motion planning to pass through singularity [26]- [31], i.e. a parallel manipulator may track a path through singular poses if its velocity and acceleration are properly constrained.…”
Section: Introductionmentioning
confidence: 99%